γ irradiation effects on natural GMZ bentonite - Liu, Wei; Liang, Dong; Yang, Zhongtian; Gao, Chao; Xie, Jingli (Physics and chemistry of minerals, 2025)
To investigate the impact of γ irradiation on bentonite, the natural bentonite from GaoMiaoZi (GMZ), located in Inner Mongolia, China, and foreseen as an engineering barrier in geological disposal facilities, was selected as the subject of this study. The sample underwent exposure to a Co-60 source followed by comprehensive analysis utilizing various techniques, including mass spectrometer, swelling pressure testing system, X-ray diffraction, simultaneous thermal analysis, infrared spectrometer, and Mössbauer spectroscopy. The findings indicated that γ irradiation detrimentally altered the microstructure and reduced the structure trivalent iron of GMZ bentonite, leading to a decrease in swelling pressure, with a noticeable cumulative dose effect. Additionally, a negative exponential correlation was observed between the maximum swelling pressure and absorbed dose. The effect of γ irradiation significantly influenced the physical and chemical properties of GMZ bentonite.